A Safe and Effective Two-Step Tract Dilation Technique in Totally Ultrasound-Guided Percutaneous Nephrolithotomy - Dong, Shao-Wei; Hu, Su-Wei; Liu, Shih-Ping; Wu, Chia-Chang; Lin, Chu-Tung; Chen, Kuan-Chou; Ho, Chen-Hsun (Urology Journal, 2022)
Purpose: To evaluate the safety and the efficacy of a radiation-free 2-step tract dilation technique in totally ultrasound-guided percutaneous nephrolithotomy (PCNL). Materials and Methods: From Oct 2018 to Mar 2020, we prospectively and consecutively enrolled 18 patients with 19 kidney units with urolithiasis. The nephrostomy tract was established by the following four steps: 1) ultrasound-guided renal puncture, 2) first-stage serial dilation to 16 Fr with Amplatz dilators, 3) check and adjustment of the partially dilated tract with a ureteroscope, 4) second-stage dilation with a 24-Fr balloon dilator. Results: The median age was 62.0 [IQR 11.0] years, and 11 (61.1%) were male. The median stone size was 3.3 [3.6] cm2, and stone laterality was almost equal over both sides. Successful tract establishment on the first attempt without fluoroscopy was achieved in 18 (94.7%) operations. The median tract establishment time was 10.4 [4.9] mins, and the median operation time was 67.0 [52.2] mins. The median hemoglobin drop was 1.0 [1.1] g/dL, and none required blood transfusion. Three (15.8%) developed fever. Pleural injury occurred in two (10.5%) operations (both had supracostal puncture), and one required drainage with pigtail. Stone-free status was achieved in 15 (77.8%) operations at 3 months postoperatively. Conclusions: Herein we present a radiation-free 2-step tract dilation technique, which is characterized by ureteroscopic check of the partially dilated tract in between the first dilation with serial fascial dilators and the second dilation with balloon. Our data suggest that it is a safe and effective method.